2005
DOI: 10.1158/1078-0432.ccr-1004-0007
|View full text |Cite
|
Sign up to set email alerts
|

Improved Tumor Targeting by Combined Use of Two Antitenascin Antibodies

Abstract: Purpose: In the pretargeted antibody-guided radioimmunotherapy (PAGRIT) system, the combined use of two different antibodies directed against the same tumor antigen could represent a valid approach for improving tumor targeting and therapeutic efficacy. We developed a novel monoclonal antitenascin antibody, ST2485, and studied its biochemical and functional properties by in vitro and in vivo assays. We then investigated the first of the three-step therapy combining ST2485 with another antitenascin antibody, ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 23 publications
0
21
1
1
Order By: Relevance
“…Furthermore, efficient tumor targeting by anti-tenascin antibodies has been shown clinically using an avidin/biotin-based pretargeting approach (37) or, more recently, with monoclonal antibodies specific for the small isoform of tenascin-C (38,39). However, all these antibodies are of murine origin and may therefore not be suitable for repeated administration to patients and for the development of biopharmaceuticals.…”
Section: I-small Immunoprotein (Sip) L19mentioning
confidence: 99%
“…Furthermore, efficient tumor targeting by anti-tenascin antibodies has been shown clinically using an avidin/biotin-based pretargeting approach (37) or, more recently, with monoclonal antibodies specific for the small isoform of tenascin-C (38,39). However, all these antibodies are of murine origin and may therefore not be suitable for repeated administration to patients and for the development of biopharmaceuticals.…”
Section: I-small Immunoprotein (Sip) L19mentioning
confidence: 99%
“…Several clinicians have tried to seek methods to increase the uptake of radiolabeled antibodies. Mixed radiolabeled antibody imaging (several mAbs of different tumor-specific antigens for the same tumor mixed for imaging after administration, namely, cocktail method of antibodies) may enhance the RII target/non-target ratio in the present study (Hay et al, 2002;Petronzelli et al, 2005). Several studies have shown that the increase in tumor radioactive uptake was not significant with the double dosage of mAb, but it increased significantly with the combined application of mAb.…”
Section: Discussionmentioning
confidence: 78%
“…Finding tumor-specific high expression antigens and methods to increase the uptake of radioactivity at the tumor site is the key to the development of lung cancer RII. Some studies have demonstrated that the application of mixed labeled antibodies to one type of cancer (called "antibody cocktail") may be an ideal methods to increase the radioactivity uptake in the tumor site (Hay et al, 2002;Petronzelli et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…107 Petronzelli et al also demonstrated improved tumor targeting with a mixture of two antitenascin antibodies in a colon carcinoma xenograft model. 108 Coadministration of 125 Ilabeled and biotinylated antitenascin antibodies ST2146 and ST2485 (directed against distinct epitopes adequately spaced to rule out stearic hindrance) exhibited additive accumulation in HT29 xenografts as compared to the individual antibodies. 108 …”
Section: Antigenic Heterogeneity and Antibody Cocktailsmentioning
confidence: 99%